CC-90001, a c-Jun N-terminal kinase (JNK) inhibitor, in patients with pulmonary fibrosis: design of a phase 2, randomised, placebo-controlled trial. Issue 1 (20th January 2022) - Popmihajlov, Zoran; Sutherland, Donna J; Horan, Gerald S; Ghosh, Atalanta; Lynch, David A; Noble, Paul W; Richeldi, Luca; Reiss, Theodore F; Greenberg, Steven
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive and often fatal interstitial lung disease (ILD); other ILDs have a progressive, fibrotic phenotype (PF-ILD). Antifibrotic agents can slow but not stop disease progression in patients with IPF or PF-ILD. c-Jun N-terminal kinases (JNKs) are stress-activated protein kinases implicated in the underlying mechanisms of fibrosis, including epithelial cell death, inflammation and polarisation of profibrotic macrophages, fibroblast activation and collagen production. CC-90001, an orally administered (PO), one time per day, JNK inhibitor, is being evaluated in IPF and PF-ILD. Methods and analysis: This is a phase 2, randomised, double-blind, placebo-controlled study evaluating efficacy and safety of CC-90001 in patients with IPF (main study) and patients with PF-ILD (substudy). Both include an 8-week screening period, a 24-week treatment period, up to an 80-week active-treatment extension and a 4-week post-treatment follow-up. Patients with IPF (n=165) will be randomised 1:1:1 to receive 200 mg or 400 mg CC-90001 or placebo administered PO one time per day; up to 25 patients/arm will be permitted concomitant pirfenidone use. Forty-five patients in the PF-ILD substudy will be randomised 2:1 to receive 400 mg CC-90001 or placebo. The primary endpoint is change in per cent predicted forced vital capacity from baseline to Week 24 in patients with IPF. Ethics and dissemination: This study will be conducted in accordance with Good Clinical Practice guidelines, Declaration of Helsinki principles and local ethical and legal requirements. Results will be reported in a peer-reviewed publication. Trial registration number: NCT03142191 .